A national crime : the Canadian government and the residential school system, 1879 to 1986 - Milloy, John S. (Critical studies in native history, 2017)
"For over 100 years, thousands of Aboriginal children passed through the Canadian residential school system. Begun in the 1870s, it was intended, in the words of government officials, to bring these children into the "circle of civilization," the results, however, were far different. More often, the schools provided an inferior education in an atmosphere of neglect, disease, and often abuse. Using previously unreleased government documents, historian John S. Milloy provides a full picture of the history and reality of the residential school system. He begins by tracing the ideological roots of the system, and follows the paper trail of internal memoranda, reports from field inspectors, and letters of complaint. In the early decades, the system grew without planning or restraint. Despite numerous critical commissions and reports, it persisted into the 1970s, when it transformed itself into a social welfare system without improving conditions for its thousands of wards. A National Crime shows that the residential system was chronically underfunded and often mismanaged, and documents in detail and how this affected the health, education, and well-being of entire generations of Aboriginal children."--